The Effect of Capital Adequacy Ratio, Loan to Deposit Ratio, Exchange Rate, and Gross Domestic Product on Non-Performing Loans with Inflation as a Moderating Variable in National Private Banks in Indonesia - Lutfiyanti; Lalu Hamdani Husman; Siti Aisyah Hidayati (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), exchange rate, and Gross Domestic Product (GDP) on Non-Performing Loans (NPL) with inflation as a moderating variable in national private banks in Indonesia. This study uses a quantitative approach with panel data for the 2019–2023 period. The research sample consisted of 38 national private banks selected using purposive sampling technique. The analytical method used is panel data regression with Random Effect Model (REM) and Moderated Regression Analysis (MRA). The results show that CAR and LDR have a positive and significant effect on NPL, the exchange rate has a negative and significant effect on NPL, while GDP has no significant effect on NPL. Inflation is unable to moderate the influence of CAR, LDR, and exchange rate on NPL, but is proven to moderate the relationship between GDP and NPL. This research provides important implications for banking management and policy makers in maintaining the stability of the banking sector.